Micron-sized elastic polymer microspheres for oil-based drilling fluid and preparation method and application thereof
By preparing methyl methacrylate and butyl acrylate copolymer microspheres, the problem of unstable plugging material in high temperature, high pressure and fractured formations was solved, and effective plugging was achieved under the conditions of bottom hole pressure fluctuation and formation breathing.
Patent Information
- Application Number
- CN202611307147.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-11-06
AI Technical Summary
Existing plugging materials are ineffective under high temperature, high pressure and fractured formation conditions, and are prone to loosening and backflow, failing to effectively cope with bottom hole pressure fluctuations and formation breathing.
Micron-sized elastic polymer microspheres were prepared by suspension polymerization using methyl methacrylate and butyl acrylate as comonomers and N,N′-methylenebisacrylamide as a crosslinking agent. The microspheres can elastically deform and embed themselves under bottom hole pressure fluctuations to form a tight sealing layer.
It improves the adaptability of the plugging layer, reduces the risk of particle loosening and backflow, enhances the stability and plugging effect of the plugging layer, and adapts to bottom hole pressure fluctuations and formation breathing.
Smart Images

Figure CN123042243A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oilfield chemistry and drilling fluid leak prevention and plugging materials, specifically to a micron-sized elastic polymer microsphere made of methyl methacrylate and butyl acrylate as comonomers and N,N′-methylenebisacrylamide as a crosslinking agent, its suspension polymerization preparation method, and its application in oil-based drilling fluid fracture plugging and formation pressure-bearing capacity enhancement. Background Technology
[0002] As oil and gas exploration extends into deeper, ultra-deep, and deepwater areas, the challenges of high-temperature, high-pressure, and fractured formations in drilling operations are becoming increasingly prominent. When the wellbore pressure or circulating equivalent density exceeds the formation's pressure-bearing limit, drilling fluid may infiltrate the formation through natural fractures, drilling-induced fractures, and high-permeability channels, leading to engineering problems such as lost circulation, abnormal bottom hole pressure, wellbore instability, and stuck pipe. Oil-based drilling fluids are expensive to prepare, and losses increase material consumption and reduce the safety and continuity of drilling operations. During pump start-up, pump shutdown, tripping, and displacement adjustment, the bottom hole pressure changes. Fractures may open as pressure increases and close as pressure decreases, leading to periodic leakage and backflow of drilling fluid between the wellbore and the formation, resulting in formation breathing. Conventional plugging materials such as calcium carbonate, walnut shells, and ordinary resins are primarily rigid particles, relying mainly on bridging, accumulation, and mechanical embedding to construct the sealing layer. Due to the limited elastic deformation capacity of these particles, under repeated bottom hole pressure fluctuations and periodic opening and closing of fractures, the particle contact relationship and pressure-bearing chain are easily altered, leading to particle loosening, backflow, bridge collapse, or the reformation of fluid channels within the sealing layer. Polymer microspheres, with their small particle size, good dispersibility, and deformability, can enter microfractures, rough depressions, and the pores within the rigid particle skeleton under pressure differential. After entering the leakage channels, the microspheres improve the density of the sealing layer through elastic compression, deformation embedding, and multi-stage filling. When the fracture width changes with the bottom hole pressure, the elastic microspheres can undergo reversible deformation within a certain range, compensating for the gaps between particles and maintaining contact with the fracture wall, thereby improving the adaptability of the sealing layer to pressure fluctuations and formation breathing. To balance the temperature stability, elastic deformation capacity, oil absorption and swelling properties, and preparation cost of polymer microspheres, this invention selects methyl methacrylate and butyl acrylate as the main polymerizing monomers, N,N′-methylenebisacrylamide as the crosslinking agent, and benzoyl peroxide as the initiator to prepare micron-sized elastic polymer microspheres via suspension polymerization. Methyl methacrylate is widely available and has high polymerization activity; its polymeric segments possess good rigidity, mechanical strength, and thermal deformation stability, providing a basic structural framework for the polymer microspheres and reducing the risk of excessive softening, adhesion, or destruction of the microspheres under high temperature and pressure differentials. Compared to ordinary rigid plugging particles, the polymer microspheres prepared in this invention possess certain structural strength, oil absorption and expansion capacity, and elastic deformation capacity through the synergistic effect of rigid methyl methacrylate segments, flexible oleophilic butyl acrylate segments, and an N,N′-methylenebisacrylamide crosslinking network. After entering the fracture, the microspheres can expand moderately under the influence of the oil phase and undergo elastic compression and deformation under pressure differential, filling the pores between particles and the irregular spaces on the fracture wall. When the bottom hole pressure fluctuates or the fracture periodically opens and closes, the microspheres can maintain the contact state of the plugging layer through elastic deformation and recovery, reducing the risk of particle loosening, backflow, and instability of the plugging structure. In summary, the selected raw materials are widely available, the costs are relatively controllable, and the synthesis process is simple, showing good potential for large-scale preparation and engineering applications. Summary of the Invention
[0003] By adjusting the ratio of rigid to flexible segments and the crosslinking density, the resulting microspheres possess elastic deformation and morphological recovery capabilities under pressure, enabling them to penetrate cracks and pores in the particle skeleton to form a dense sealing layer. Once inside the cracks, the microspheres absorb the oil phase and expand moderately. Under pressure differential, they undergo elastic compression and deformation, filling the pores between particles and the irregular spaces on the crack walls, thus forming a dense and stable sealing layer. The present invention achieves the above objectives through the following technical solutions. This invention provides micron-sized elastic polymer microspheres for oil-based drilling fluids. The raw materials used include methyl methacrylate (MMA), butyl acrylate (BA), N,N′-methylenebisacrylamide (MBAA), benzoyl peroxide (BPO), polyvinyl alcohol (PVA), and deionized water. The micron-sized elastic polymer microspheres with a three-dimensional network structure are prepared using suspension polymerization, with an aqueous solution of polyvinyl alcohol as the continuous phase and suspension dispersion medium, through free radical copolymerization and crosslinking reactions. With a total mass of methyl methacrylate and butyl acrylate of 100 parts, the mass fractions of each component are as follows: 35-50 parts of methyl methacrylate 50-65 parts of butyl acrylate 2-8 parts of N,N′-methylenebisacrylamide Benzoyl peroxide 0.3-0.8 parts Polyvinyl alcohol 1.2–3.2 parts 350-450 parts deionized water Preferably, the mass ratio of butyl acrylate to methyl methacrylate is 3:2. Based on a total mass of 100 parts for both comonomers, the composition is: 60 parts butyl acrylate, 40 parts methyl methacrylate, 5 parts N,N′-methylenebisacrylamide, 0.5 parts benzoyl peroxide, 2 parts polyvinyl alcohol, and 400 parts deionized water. The polyvinyl alcohol has a mass concentration of 0.3% to 0.8% in the aqueous phase, preferably 0.5%; the total mass of methyl methacrylate and butyl acrylate is 20% to 30% of the mass of deionized water, preferably 25%; the amount of N,N′-methylenebisacrylamide is 2% to 8% of the total mass of the two comonomers, preferably 5%; and the amount of benzoyl peroxide is 0.3% to 0.8% of the total mass of the two comonomers, preferably 0.5%. The preparation method of the micron-sized elastic polymer microspheres includes the following steps: First, add deionized water to a three-necked flask, install a mechanical stirrer at the middle neck, and place the flask in a constant temperature water bath and heat it to 80–90 °C. Slowly add polyvinyl alcohol (PVA) while stirring, and continue stirring for 45–75 minutes to ensure complete dissolution of the PVA, obtaining a PVA dispersion with a mass concentration of 0.3%–0.8%. Then cool the dispersion for later use. The second step involves weighing methyl methacrylate and butyl acrylate according to the formula, adding the two comonomers to a beaker, and mixing them under magnetic stirring for 20–40 minutes. N,N′-methylenebisacrylamide is then added to the mixed monomers, and stirring continues for 45–75 minutes to ensure uniform dispersion of the crosslinking agent, resulting in a reactive monomer mixture. Third, adjust the temperature of the constant temperature water bath to 55-65 ℃, turn on the mechanical stirrer and adjust the stirring speed to 400-600 r / min. Slowly add the reactant monomer mixture to the polyvinyl alcohol dispersion to form a stable oil-in-water suspension droplet; then add benzoyl peroxide and continue stirring for 20-40 min to carry out the initial polymerization. The fourth step involves heating the reaction system to 68–72 °C and reacting for 1.5–2.5 h, then further heating to 82–88 °C and reacting for another 1.5–2.5 h to ensure complete polymerization of the remaining monomers. During polymerization, the stirring speed is maintained at 400–600 r / min, preferably 500 r / min. Fifth step: After the reaction is complete, cool the system to room temperature and wash the product repeatedly with deionized water and anhydrous ethanol to remove residual polyvinyl alcohol, unreacted monomers, and oligomers. Filter or vacuum filter the washed product and dry it in an oven at 55–65 °C for 20–28 h to obtain micron-sized elastic polymer microspheres. (See [link to product description]). Figure 1 . The methyl methacrylate forms relatively rigid polymer segments, which are used to improve the structural strength, shape retention and compressive support of the microspheres; The butyl acrylate forms flexible polymer segments, which are used to reduce the polymer's glass transition tendency and improve the elastic deformation capability of the microspheres. The N,N′-methylenebisacrylamide, as a bifunctional crosslinking agent, is used to form a three-dimensional crosslinking network between copolymer segments to prevent the microspheres from dissolving, sticking together, and becoming excessively softened after absorbing oil or being heated. Benzoyl peroxide is a free radical initiator. It should be noted that the standard Chinese name for BPO is benzoyl peroxide, not formamide peroxide. The polyvinyl alcohol is a suspending and dispersing agent used to reduce the risk of droplet aggregation and particle adhesion, and its concentration and stirring speed can be used to adjust the microsphere size and particle size distribution. The particle size of the polymer microspheres can be adjusted by the polyvinyl alcohol concentration, stirring speed, and comonomer feeding speed, with a preferred particle size range of 50–500 μm. The polymer microspheres can be added alone to oil-based drilling fluids at a dosage of 1% to 5% of the total mass of the oil-based drilling fluid, preferably 3%. They can also be compounded with one or more of calcium carbonate, barite, elastic graphite, sheet materials, fiber materials, or nano-silica for synergistic sealing of microcracks, sand bed pores, and internal pores of rigid particle skeletons. Compared with the prior art, the present invention has at least the following beneficial effects: (1) The copolymerization of methyl methacrylate and butyl acrylate allows the microspheres to contain both relatively rigid support segments and flexible segments, thereby improving the ability to deform under pressure and recover from pressure relief while maintaining the particle shape. (2) Using N,N′-methylenebisacrylamide to construct a three-dimensional cross-linked network and controlling its amount to 2% to 8% of the total mass of the comonomer can reduce the risk of oil absorption and adhesion caused by insufficient cross-linking and the risk of decreased elasticity caused by excessive cross-linking. (3) Using polyvinyl alcohol to stabilize the water-in-oil suspension droplets and combining it with a segmented heating polymerization process can reduce droplet aggregation and particle agglomeration, resulting in microspheres with better sphericity, dispersibility and adjustable particle size. (4) Microspheres can enter the microcracks and the pores inside the particle skeleton under pressure difference. They can improve the tightness of the sealing layer through elastic compression, deformation embedding and pore filling. They can also compensate for local gaps during the periodic opening and closing of cracks, and improve the sealing layer's adaptability to formation breathing and bottom hole pressure fluctuations. (5) The preparation process involves only conventional operations such as dissolution, mixing, suspension polymerization, washing and drying. The raw materials are widely available, the process equipment is simple, and it is easy to control the particle size and carry out large-scale production. Attached image description: Figure 1 This is a schematic diagram of SEM scanning of polymer microspheres. Figure 2 This is a schematic diagram of the F-1 type high-temperature and high-pressure crack sealing instrument. Figure 3This is a diagram showing the temperature and pressure control interface during the experiment. Figure 4 This is a diagram illustrating the heating and pressurization process during a high-temperature, high-pressure sealing test. Figure 5 This is a photograph of the sealing layer in the cracked plate after a high-temperature and high-pressure sealing test. Figure 6 This is the TG-DTG curve of the polymer microspheres. Figure 7 The graph shows the change in the oil absorption mass of polymer microspheres in No. 3 white oil and diesel oil. Detailed implementation method: The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments. Unless otherwise specified, the amounts of each component in the following embodiments are by mass, and the mechanical stirrer, constant temperature water bath, magnetic stirrer, vacuum filter and drying oven used are all commonly used equipment in the art. In the following examples, the amount of deionized water used was 100.0 g; polyvinyl alcohol was used as a suspending dispersant; benzoyl peroxide was used as a free radical initiator; and N,N′-methylenebisacrylamide was used as a crosslinking agent. Example 1: Micron-sized elastic polymer microspheres with a preferred formulation were prepared using the following steps: First, add 100.0 g of deionized water to a three-necked flask, adjust the water bath temperature to 85 ℃, add 0.50 g of polyvinyl alcohol under stirring and continue stirring for 1 h to obtain a polyvinyl alcohol dispersion with a mass concentration of about 0.5%, and cool it for later use. In the second step, weigh 10.0 g of methyl methacrylate and 15.0 g of butyl acrylate, mix them on a magnetic stirrer for 30 min, add 1.25 g of N,N′-methylenebisacrylamide and 0.125 g of benzoyl peroxide, and continue stirring for 1 h to obtain a reaction monomer mixture containing an initiator. Third, adjust the water bath temperature to 60 ℃ and set the mechanical stirring speed to 500 r / min. Slowly add the reaction monomer mixture containing the initiator to the polyvinyl alcohol dispersion and stir for 30 min. The fourth step is to heat the reaction system to 70 ℃ for 2 h, and then heat it to 85 ℃ for 2 h. The stirring speed is kept at 500 r / min throughout the polymerization process. Fifth step: After the reaction is complete, cool to room temperature, wash with deionized water and anhydrous ethanol alternately 3 to 5 times, filter, and dry the product in a 60 ℃ oven for 24 h to obtain micron-sized elastic polymer microspheres. Example 2: Except for adjusting the amount of N,N′-methylenebisacrylamide to 0.75 g, which is 3% of the total mass of the two comonomers, the amounts of other raw materials and the preparation steps were the same as in Example 1. This example was used to investigate the effect of a lower crosslinking density on the oil absorption and swelling capacity, elastic recovery, and particle adhesion tendency of the microspheres. Example 3: Except for adjusting the amount of N,N′-methylenebisacrylamide to 1.75 g, which is 7% of the total mass of the two comonomers, the amounts of other raw materials and the preparation steps were the same as in Example 1. This example was used to investigate the effect of higher crosslinking density on the structural strength, compressive deformation capacity, and oil absorption and swelling properties of the microspheres. Example 4: 11.25 g of methyl methacrylate and 13.75 g of butyl acrylate were weighed to adjust the mass ratio of butyl acrylate to methyl methacrylate to 55:45. The amounts of N,N′-methylenebisacrylamide, benzoyl peroxide, polyvinyl alcohol, and deionized water were 1.25 g, 0.125 g, 0.50 g, and 100.0 g, respectively. The remaining preparation steps were the same as in Example 1. This example was used to investigate the changes in the morphology retention and elastic deformation properties of microspheres after increasing the proportion of rigid monomers. Table 1. Raw material ratios for Examples 1-4 Example MMA / g BA / g MBAA / g BPO / g PVA / g Water / g Stirring speed (r / min) Example 1 10.00 15.00 1.25 0.125 0.50 100.0 500 Example 2 10.00 15.00 0.75 0.125 0.50 100.0 500 Example 3 10.00 15.00 1.75 0.125 0.50 100.0 500 Example 4 11.25 13.75 1.25 0.125 0.50 100.0 500 Performance Evaluation and Plugging Examples 1. High-temperature and high-pressure sealing evaluation device The F-1 high-temperature, high-pressure fracture plugging device was used to evaluate oil-based drilling fluids containing polymer microspheres. This device can independently monitor the test temperature, container pressure, and fracture pressure, and simulate leakage channels of different widths using replaceable fracture plates. 2. Preparation of oil-based slurry The oil-based slurry consists of diesel oil, 2.5% primary emulsifier, 1.5% secondary emulsifier, 1% wetting agent, 3% organic clay, 2.5% filtration reducer, 2% CaO, 26% CaCl2 aqueous solution, 6% cement-based plugging particles, and barite. In the control group, no polymer microspheres were added; in the microsphere group, polymer microspheres accounting for 4% of the total drilling fluid mass were added to the above-mentioned slurry. 3. High-Temperature and High-Pressure Crack Sealing Methods The prepared oil-based drilling fluid was loaded into a high-temperature, high-pressure fracture plugging device, and 1 mm and 3 mm fracture plates were installed. The temperature and pressure were gradually increased to 230 ℃ and 10 MPa, and the cumulative leakage, plugging time, and post-plugging condition were recorded during the test. The plugging time was calculated from the start of pressurization until the leakage rate significantly decreased and a stable plugging layer was formed. After the test, the plugging layer was checked for backflow or failure. 4. Example 5: High-temperature and high-pressure plugging performance of 4% polymer microspheres 4% of the polymer microspheres prepared in Example 1 were added to the above oil-based slurry. Plugging tests were conducted using 1 mm and 3 mm crack plates at 230 °C and 10 MPa. The high-temperature, high-pressure crack plugging instrument, temperature and pressure control interface, and temperature-pressure rise curves are shown below. Figure 2 , Figure 3 , Figure 4 The experimental results are shown in Table 2. Table 2. Blocking performance of oil-based slurry and system containing 4% polymer microspheres Experimental system Crack width / mm Temperature / °C Pressure / MPa Cumulative leakage / mL Blocking time / min Post-sealing status Blank oil-based slurry 1 230 10 169 15 Large leakage Blank oil-based slurry 3 230 10 247 15 Large leakage Oil-based slurry + 4% microspheres 1 230 10 23 4 No backflow, no failure Oil-based slurry + 4% microspheres 3 230 10 25 4 No backflow, no failure Compared with blank oil-based slurry, the addition of 4% polymer microspheres reduced the cumulative leakage of 1 mm cracks from 169 mL to 23 mL, a reduction of 86.4%; and the cumulative leakage of 3 mm cracks from 247 mL to 25 mL, a reduction of 89.9%. The sealing time under both crack conditions was reduced from 15 min to 4 min, a reduction of 73.3%. No backflow or failure of the sealing layer was observed after sealing was completed at 230 ℃ and 10 MPa, indicating that the polymer microspheres can enter the gaps between rigid particle skeletons and irregular spaces in cracks under high temperature and high pressure oil-based environments, improving the density and stability of the sealing layer through oil absorption deformation and elastic embedding. The crack plate after sealing is shown in the figure. Figure 5 . 5. Thermal stability evaluation Thermogravimetric-differential thermogravimetric analysis (TG-DTG) was used to evaluate the thermal stability of the polymer microspheres obtained in Example 1. The TG-DTG curves are shown below. Figure 6 The test results show that the 5% weight loss temperature of the sample is approximately 245.66 ℃; the initial temperature of the main thermal decomposition stage is approximately 297.7 ℃, the midpoint temperature is approximately 345.1 ℃, and the termination temperature is approximately 392.5 ℃; the DTG peak temperature is 343.3 ℃, and the maximum weight loss rate is approximately 10.12% / min. At the end of the test, the total weight loss of the sample is approximately 93.44%, and the residual mass is approximately 6.56%. These results indicate that the microspheres maintain good overall thermal stability up to approximately 245 ℃, meeting the temperature requirements for high-temperature plugging evaluation of oil-based drilling fluids at 230 ℃. 6. Evaluation of oil absorption and weight gain performance 2.00 g of dried polymer microspheres were weighed and placed in No. 3 white oil and diesel oil respectively. Samples were taken at specified times, and after filtering and removing free oil from the particle surface, the samples were weighed. The oil absorption weight gain rate S was calculated as S = (m t The calculation is based on (-m0) / m0×100%, where m0 is the mass of the dried microspheres before soaking, and m t The mass of the microspheres after soaking for time t and removing the free oil on the surface. Depend on Figure 7It can be seen that the mass of the microspheres in both oil phases increases with time after oil absorption, with a faster increase in the first 20 hours, followed by a gradual decrease and stabilization. After 80 hours of soaking, the mass of the No. 3 white oil group was approximately 5.40 g, and the mass of the diesel oil group was approximately 4.40 g, corresponding to oil absorption weight gain rates of approximately 170% and 120%, respectively. The oil absorption weight gain of the No. 3 white oil group was higher than that of the diesel oil group, indicating that the properties of the oil phase affect the oil absorption behavior of the microspheres. This experiment can prove the mass increase of the microspheres after absorbing the oil phase; if the volume expansion ratio needs to be expressed, further determination should be made in conjunction with microparticle size or volume change experiments. 7. Comparative Analysis Although the blank oil-based slurry contains 6% cement-based plugging particles, it still suffers from problems such as large gaps in the particle skeleton, long sealing time, and high cumulative leakage in 1-3 mm cracks. After adding polymer microspheres, the microspheres can deform under pressure differential, filling the gaps between cement-based particles and local pores on the crack walls, thus transforming the single rigid particle bridging into a composite plugging structure of "rigid skeleton support - elastic microsphere filling." This structure exhibits significant leakage reduction and rapid plugging effects on 1-3 mm cracks at 230 ℃ and 10 MPa.
Claims
1. A micron-sized elastic polymer microsphere for oil-based drilling fluids, characterized in that, The polymer microspheres are prepared by suspension polymerization of raw materials comprising methyl methacrylate, butyl acrylate, N,N′-methylenebisacrylamide, benzoyl peroxide, polyvinyl alcohol, and deionized water. Based on a total mass of 100 parts of methyl methacrylate and butyl acrylate, the raw materials include: 35-50 parts of methyl methacrylate, 50-65 parts of butyl acrylate, 2-8 parts of N,N′-methylenebisacrylamide, 0.3-0.8 parts of benzoyl peroxide, 1.2-3.2 parts of polyvinyl alcohol, and 350-450 parts of deionized water, wherein the sum of the mass parts of methyl methacrylate and butyl acrylate is 100 parts. The methyl methacrylate and butyl acrylate form copolymer segments, and the N,N′-methylenebisacrylamide forms a three-dimensional cross-linked network between the copolymer segments.
2. The micron-sized elastic polymer microspheres for oil-based drilling fluids according to claim 1, characterized in that, Based on a total mass of 100 parts of methyl methacrylate and butyl acrylate, the methyl methacrylate comprises 40 parts, the butyl acrylate comprises 60 parts, the N,N′-methylenebisacrylamide comprises 5 parts, the benzoyl peroxide comprises 0.5 parts, the polyvinyl alcohol comprises 2 parts, and the deionized water comprises 400 parts.
3. The micron-sized elastic polymer microspheres for oil-based drilling fluids according to claim 1 or 2, characterized in that, The polyvinyl alcohol has a mass concentration of 0.3% to 0.8% in the aqueous phase, and the total mass of methyl methacrylate and butyl acrylate is 20% to 30% of the mass of deionized water.
4. The micron-sized elastic polymer microspheres for oil-based drilling fluids according to any one of claims 1 to 3, characterized in that, The polymer microspheres have a particle size of 50–500 μm.
5. The micron-sized elastic polymer microspheres for oil-based drilling fluids according to any one of claims 1 to 4, characterized in that, The polymer microspheres can absorb the oil phase and expand, and under pressure difference, they can generate elastic compression and deformation to fill the irregular space on the crack wall and the pores inside the rigid particle skeleton.
6. A method for preparing micron-sized elastic polymer microspheres for oil-based drilling fluids according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Add polyvinyl alcohol to deionized water at 80-90 °C and dissolve it under stirring for 45-75 min to obtain a polyvinyl alcohol dispersion with a mass concentration of 0.3%-0.8%; (2) Mix methyl methacrylate and butyl acrylate for 20-40 min, add N,N′-methylenebisacrylamide and continue mixing for 45-75 min to obtain a mixture of reaction monomers; (3) Under stirring conditions of 55-65 °C and 400-600 r / min, the reaction monomer mixture is added to the polyvinyl alcohol dispersion to form an oil-in-water suspension droplet, benzoyl peroxide is added and reacted for 20-40 min; (4) Heat the reaction system to 68-72 °C and react for 1.5-2.5 h, then heat to 82-88 °C and react for 1.5-2.5 h to obtain the polymerization product; (5) The polymer product is cooled, washed, and separated into solid and liquid components, and then dried at 55-65 °C for 20-28 h to obtain the micron-sized elastic polymer microspheres.
7. The preparation method according to claim 6, characterized in that, The mass concentration of the polyvinyl alcohol dispersion in step (1) is 0.5%; the stirring speed in steps (3) and (4) is 500 r / min; in step (4), the reaction is first carried out at 70 ℃ for 2 h, and then at 85 ℃ for 2 h; in step (5), the mixture is washed 3 to 5 times with deionized water and anhydrous ethanol alternately, and then dried at 60 ℃ for 24 h.
8. The preparation method according to claim 6 or 7, characterized in that, The particle size of the polymer microspheres is adjusted to 50–500 μm by adjusting at least one of the following: polyvinyl alcohol concentration, stirring speed, and feeding speed of the reaction monomer mixture.
9. The application of the micron-sized elastic polymer microspheres for oil-based drilling fluids according to any one of claims 1 to 5 in the preparation of oil-based drilling fluid fracture sealing materials or formation pressure-bearing capacity enhancement materials.
10. The application according to claim 9, characterized in that, The amount of polymer microspheres added is 1% to 5% of the total mass of the oil-based drilling fluid.
11. The application according to claim 9 or 10, characterized in that, The polymer microspheres are compounded with one or more of calcium carbonate, barite, elastic graphite, sheet materials, fiber materials, and nano-silica to seal microcracks, sand bed pores, or internal pores of rigid particle skeletons.
12. The application according to any one of claims 9 to 11, characterized in that, The oil-based drilling fluid is used in fractured formations with temperatures not exceeding 230 °C, and the polymer microspheres construct a sealing layer through oil absorption expansion, elastic compression, and deformation embedding.
